Identification and physiological activity of (methoxymethyl)triphenylphosphonium chloride as a new phytotoxin isolated from Rhizoctonia solani AG-3 TB - Li, Xinchun; Hou, Huihui; Li, Bin; Guo, Shiping; Jiang, Lianqiang; Xu, Chuantao; Xie, Yunbo; An, Mengnan; Zhang, Chong; Wu, Yuanhua (Frontiers in Plant Science, 2023)
Rhizoctonia solani as a cosmopolitan fungus is the causative agent of many crop diseases and leads to significant economic losses in crop production. To explore the toxin structure and physiological activity of R. solani AG-3 TB, high-performance liquid chromatography (HPLC), infrared absorption spectrum (IR), and nuclear magnetic resonance spectrum (NMR) were required. Here, the compound (methoxymethyl)triphenylphosphonium chloride (MMC) with the molecular formula C20H20ClOP was purified and identified from R. solani AG-3 TB. The pure compound MMC treated at 20 μg/mL, 50 μg/mL, and 100 μg/mL can cause obvious necrosis on leaves, increase active oxygen species (AOS), decrease chlorophyll content, and damage cellular structure. The results enrich the understanding of toxin compounds for R. solani and provide valuable insights into the toxicology of R. solani AG-3 TB.